2004
DOI: 10.1590/s0104-66322004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of environmental impact criteria in the design and operation of chemical processes

Abstract: -Environmental impact assessment is becoming indispensable for the design and operation of chemical plants. Structured and consistent methods for this purpose have experienced a rapid development. The more rigorous and sophisticated these methods become, the greater is the demand for convenient tools. On the other hand, despite the incredible advances in process simulators, some aspects have still not been sufficiently covered. To date, applications of these programs to quantify environmental impacts have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Paralleling work done on material efficiency green metrics specific to stand-alone individual reactions and synthesis plans, considerable research has been done on life cycle assessment (LCA) (sometimes called life cycle analysis in the literature , ) to assess the environmental impact of chemical processes from a holistic point of view. This subject has been extensively reviewed and historical accounts of its origin have been published. , Here we briefly describe its approaches and how the present analysis differs from it.…”
Section: Introductionmentioning
confidence: 99%
“…Paralleling work done on material efficiency green metrics specific to stand-alone individual reactions and synthesis plans, considerable research has been done on life cycle assessment (LCA) (sometimes called life cycle analysis in the literature , ) to assess the environmental impact of chemical processes from a holistic point of view. This subject has been extensively reviewed and historical accounts of its origin have been published. , Here we briefly describe its approaches and how the present analysis differs from it.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of dynamic simulation applications for optimizing energy and chemical systems are shown in [3,4], while applications of discrete event simulation to the optimization of industrial systems can be found in [4][5][6]. Usage of simulation in specific situations are presented in [7] for sustainable plant design, in [8] for gasifier pressure modeling, and in [9] for analyzing a petrochemical process wastewater plant. Additional applications include treating a desalination plant [10], optimizing the drying of phosphates [11], analyzing the benzene-toluene-xylene separation train from a sustainable point of view [12].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Minimal studies on exploiting LCA to analyse the environmental impact of propylene oxide and its derivatives are presented in the literature. In one of the few studies, Bauer and Maciel (2004) studied the propylene glycol's production transient state operation from propylene oxide by using LCA analysis, which can be interpreted as gate-to-gate analysis for propylene oxide. They considered both environmental impacts and traditional economic evaluation during the process design.…”
Section: Introductionmentioning
confidence: 99%